Health promotion through sport: international sport federations' priorities, actions and opportunities. Issue 1 (12th July 2017) - Mountjoy, Margo; Costa, A; Budgett, R; Dvorak, J; Engebretsen, L; Miller, S; Moran, J; Foster, J; Carr, J
Abstract : Objective: To identify areas of priority and activity for international sportsfederations (IFs) with respect to athlete health and safety, and global health. Results serve to direct the work of the Association of Summer Olympic IF Medical and Scientific Consultative Group, the International Olympic Committee and to influence IFs' planning and priorities. Methods: The 28 IFs participating in the Summer Olympic Games (2016) were asked to rank the relative importance of 11 health-related topics and to report their activities or research initiatives on 27 identified topics using an electronic survey. A comparison with a similar survey (2012) was made. Results: The response rate was 100%. In general, the ' fight against doping ' had the highest priority followed by 'image as a safe sport '. The topics with the lowest importance ratings were ' increasing the number of elite athletes ', and ' health of the general population '. Despite ranking ' health of your athletes, ' as a top priority, IFs are not addressing all aspects of athlete health. In comparison with 2012, there was a significant decrease in priority for IFs is ' health of the general population '. Conclusion: Despite the widespread knowledge of the importance of the promotion of physical activity (sport) on global health, the decreasing priority and programming of the IFs on physical activity promotion is concerning. Although IFs have prioritised the protection of the health of elite athletes, there are gaps in programming demonstrating that IFs are missing important areas of athlete health. Improving recreational athlete health programming could also benefit population health as well as improve IF fan base and sport participation.